MODEL-MODEL EPISTEMOLOGI ISLAM - Soleh, A Khudori (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2005)
As well as in the West and the Orient, Islam also recognizes system of thought which include foundation, method, and application. There are at least three models of epistemology in Islamic thought system that is Bayani, Burhani, and Irfani.Bayani is the system of thought, which based his way of thinking on the text, while burhani is the system of thought which based on ratio, and ‘irfani based on intuition. They use methods; exploration of text meaning for bayani. Those three models of epistemology have much contribution on developing Islamic knowledge and sciences. Bayani emerges fiqh and Islamic theology, while burhani comes out Islamic Philosophy, and irfani appears whereas burhani uses trick of ratio, and irfani works on heart purified.Sufism.Keywords: Bayani, Burhani and Irfani